Adult vaccination in three Eastern Mediterranean countries: current status, challenges and the way forward - Iftihar Koksal; Salah Al Awaidy; Abdullah Mufareh Assiri; Onur Ozudogru; Mansour Khalaf; Cihan Yeşiloğlu; Selim Badur (Taylor & Francis Group, 2024)
Introduction Changing population demographics places a premium on optimizing older adult health. Vaccine-preventable diseases represent a substantial clinical and economic burden in older adults (≥65 years).Areas covered This narrative review summarizes the adult immunization landscape in three countries; Saudi Arabia, the United Arab Emirates and Türkiye, informed by literature searches; Pubmed (23-27 September 2023) supplemented by citation tracking via Google Scholar). Existing vaccination recommendations and published data were reviewed to evaluate vaccine uptake, chiefly focusing on core adult vaccines (seasonal influenza, pneumococcal and herpes zoster). Barriers to vaccine access and uptake were reviewed, and initiatives to improve recommended vaccine uptake in older (≥65 years) or otherwise high-risk adults are described.Expert Opinion Uptake of recommended adult vaccines is low in all three countries. Receipt of annual seasonal influenza vaccine is typically below 50% in both older and at-risk younger adults; pneumococcal vaccination rates are even lower in eligible adults (<15% and often far lower), as is herpes zoster vaccine uptake (typically <5%). Low coverage is driven chiefly by low awareness of vaccine benefits, inconsistent recommendations, and vaccine hesitancy, together with often complex adult vaccine access pathways. Initiatives and remedies aimed at augmenting adult vaccination rates are warranted.